Defibrillation Threshold Testing After ICD Implantation in Patients with Chronic Kidney Disease - Rohit J. Timal; Lano Osman; Joris I. Rotmans; Marianne Bootsma; Bart Mertens; Martin J. Schalij; Ton J. Rabelink; J. Wouter Jukema (Cardiology and Therapy)
Abstract Introduction Routine defibrillation threshold (DFT) testing at the time of implantable cardioverter-defibrillator (ICD) implantation is no longer recommended because testing did not improve shock efficacy or reduce arrhythmic death. However, patients with severe chronic kidney disease (CKD) were not included in these trials and might benefit from DFT testing. International guidelines shed no light on the subject of the effect of kidney function on DFT testing in patients with CKD. Methods In this retrospective study, we aimed to identify the success and safety of DFT in patients with CKD stages 1–5 (ages 55–80 years) undergoing primary transvenous ICD implantation. Results A total of 451 patients were stratified into three groups based on kidney function: group 1 with CKD stage 1–2 (n = 294), group 2 with CKD stage 3–4 (n = 90), and group 3 with CKD stage 5 (n = 67). Ventricular fibrillation was induced 827 times. The median number of threshold testing per patient was two (interquartile range 1–2; range 1–7). No evidence of between CKD-group differences in ICD defibrillation success rates could be found when using all patient attempts, regardless of correction for energy levels (p = 0.262). DFT-related complications occurred in 16 patients (3.5%), predominantly hypoxemia due to hypoventilation (1.6%) and atrial arrhythmias. Five patients (1.1%) underwent ICD or lead revision following abnormal DFT test results. Conclusions We did not demonstrate a correlation between CKD and increased DFT or an increased rate of inadequate defibrillation safety margin. DFT testing is feasible with a low risk of serious complications in patients with moderate and advanced CKD when clinically deemed necessary. DFT testing is not routinely required in patients with (advanced) CKD.